Grade Expectations: Rationality and Overconfidence - Jan R. Magnus; Anatoly A. Peresetsky (Tinbergen Institute, 2017)
Overconfidence seems to be an essential aspect of human nature, and one way to study overconfidence is to consider students' forecasts of their exam grades. Part of a student's grade expectation is based on the student's previous academic achievements; what remains can be interpreted as (over)confidence. In this paper we study overconfidence using a sample of about five hundred second-year undergraduate students enrolled in a statistics course in Moscow. The course contains three exams and each student produces a forecast for each of the three exams. Students' expectations are not rational and most of students are overconfident, which is in agreement with what most people find. Less obvious findings are that overconfidence is helpful: given the same academic achievement students with larger confidence get higher exam grades. Female students are less overconfident than male students, their forecasts are more rational, and they are also faster learners in the sense that they adjust their expectations more rapidly.
Keywords: 330; Rational expectations; Classroom experiment; Overconfidence; Gender difference; Persistence